Interpersonal-driven features in research article abstracts: cross-disciplinary metadiscoursal perspective - Khedri, Mohsen; Chan, Swee Heng; Tan, Helen (Universiti Putra Malaysia Press, 2015)
Being a specific communicative genre of disseminating knowledge in today's academic arena, the research article abstract has its own specific conventional structure. Through such a seminal genre, research article writers are able to ratify and contribute their own new findings to the research community they belong to. Taking a cross-disciplinary quantitative approach, this study explores the status of interactional metadiscourse markers as prevalent interpersonal-driven features in research article abstracts. The central objective is to investigate how research article writers in particular discipline tackle and deploy interactional metadiscourse markers in the abstract section of their papers in the effort to propagate their ideas. Hyland's (2005) taxonomy of metadiscourse was adopted to analyse sixty research article abstracts written in two disciplines (Applied Linguistics and Economics) sourced from discipline-specific journals. As found, variations across the two fields of knowledge studied were enormously marked. Results of the present research may be of help for research article writers, particularly novice writers, to learn more about the socio-rhetorical conventions and prevalent discursive strategies established in their own specific disciplinary community.